2016
DOI: 10.5223/pghn.2016.19.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for the Weight Loss during Hospitalization in Children: A Single Korean Children’s Hospital Experience

Abstract: PurposeUndernutrition during hospitalization increases the risk of nosocomial infection and lengthens the disease courses. The aim of this study was to evaluate the risk factors of weight loss during hospitalization in children.MethodsAll the patients who were admitted in general wards between April and May 2014 were enrolled. Patients aged >18 years and discharged within 2 days were excluded. Weight loss during hospitalization was defined as a decrease in body weight of >2% in 8 hospital days or on the day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
1
8
0
3
Order By: Relevance
“…Hospitalization itself is a risk for weight lost [10], so borderline nourished patients can be considered to be at danger of developing undernutrition. In attempt to maximize the power of anthropometric measures in identifying all children that would need nutritional supervision, borderline nourished patients on admission were added to malnourished group, mounting to 50/124 patients (40.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalization itself is a risk for weight lost [10], so borderline nourished patients can be considered to be at danger of developing undernutrition. In attempt to maximize the power of anthropometric measures in identifying all children that would need nutritional supervision, borderline nourished patients on admission were added to malnourished group, mounting to 50/124 patients (40.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hospital malnutrition in children can lead even more to growth retardation and negative educational and social outcomes; as well as contributing to premature death. [2] Children and young people with special health care needs must undergo routine screening for malnutrition in admission facilities. Registered dietitian nutritionists (RDNs) or nurses in pediatric units and all of the healthcare team members must work together to ensure that the detection of malnutrition becomes an integral part of routine pediatric care.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a growing interest in preventing malnutrition in hospitalized patients, the recent study has also shown that the prevalence rate of malnutrition among hospitalized children ranged from 7.5% to 17% in Europe [ 4 5 ]. In a study in Korea, the prevalence of malnutrition among hospitalized children and adults were 12.5% and 22%, respectively [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%